Sustainable materials science and technology selected, peer reviewed papers from the International Conference Sustainable Materials Science and Technology (SMST 15), July 15-17, 2015, Paris, France - Duque de Brito, Paulo Sergio (Advanced materials research ;, 2016)
This edition contains selected papers presented to discuss worldwide results and proposals regarding to the soundest issues related to modern materials and processing technologies.